Ideal female body & diet culture: Challenges and recommendations for today’s woman - Barrera Carranza, Yamile Zureyma (2021)
In all ages, the ideal of the female body is determined by the concept of beauty of each culture, according to the traditions or problems of society. For example, in Egyptian culture, women were appreciated if they have a slim body, narrow back, small waist, long legs, and a symmetrical face. Since the year 2000 to nowadays, the ideal female body also consists of maintaining a slim complexion, but highlighting the muscular area of ​​the bust, buttocks, abdominal zone and thighs. That is why currently a woman tries to achieve this ideal of a female body in different ways, which can put physical and mental health at risk. On the one hand, she manipulates the photographs she shares on social networks; and on the other, she follows different food trend diets that do not meet the parameters of a correct diet, or worse, she adopts risky eating behaviors. It is important to promote a healthy lifestyle and not consider health only as something reductionist, immediate and fleeting; because a woman identity is made up of physical, mental and social components. Therefore, in this brief review it is recommended to practice integral health, through knowledge of scientific evidence compatible with women.